1987
DOI: 10.1002/mrc.1260250904
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR study of the structures of open‐chain bis‐reissert analogues and their salts

Abstract: The structures of open-chain bis-Reissert analogues and their salts were investigated using I3C NMR spectroscopy. Evidence is presented to show that the former exists in the acyclic form in solution. Detailed structural studies and the I3C NMR data clearly show that, in solution, the open-chain bis-Reissert salt analogues exist predominantly as the amino tautomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(1 reference statement)
2
1
0
Order By: Relevance
“…However, the mechanistic pathway for the conversion bis‐oxazolium salts to the corresponding bis‐amino acid remains to be fully elucidated. Nevertheless, our results are consistent with structural studies on other classes of Reissert compounds [21–23].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, the mechanistic pathway for the conversion bis‐oxazolium salts to the corresponding bis‐amino acid remains to be fully elucidated. Nevertheless, our results are consistent with structural studies on other classes of Reissert compounds [21–23].…”
Section: Resultssupporting
confidence: 92%
“…The bis‐oxazolium salt exists as different tautomeric forms I–III , which could interconvert in solution. We previously reported the 13 C NMR study of the representative bis‐oxazolium perchlorate salts and confirmed that the amino form II is the most predominant tautomer in solution [21]. Our results are in agreement with that of Cook et al .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation